Reflection on Implementing Blended Learning in the Translation Classroom via Edmodo - Limantoro, Singgih Widodo (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
To face the challenges of 21st century education, schools have to reform their traditional classroom by using online learning to enhance teaching and learning. Blended learning is a mixture of face-to-face learning and online learning. In translation classroom, students may use their ways for translation. They may use electronic device for translation, dictionary, or other ways to gain the desired quality of the translation output. They usually expect their translation would meet at least three quality aspects such as, accurate, natural, and communicative. To gain the quality of translation, students have to make sure that the input of the source language and the process of translation are semantically and structurally correct because it would be hard to translate the sentences which have problems, such as fragments, run-on, and non-parallel. In this paper, the writer would like to share some feedbacks from the students of the Business English Study Program of Politeknik Ubaya Surabaya Indonesia in his translation classroom by reflecting on the student learning experience in Translation. These feedbacks would help guide the students to improve the output of translation. This classroom action research findings would help the teacher encourage the students learn how to translate in better ways. In other words, the teacher would facilitate the students to become smart translators by using reflective ways to raise their awareness to gain the desired output of translation. And passion and practice might also be the key successful factors in translation classroom.